An Organelle RNA Recognition Motif Protein Is Required for Photosystem II Subunit psbF Transcript Editing. Issue 4 (17th February 2017) - Hackett, Justin B.; Shi, Xiaowen; Kobylarz, Amy T.; Lucas, Meriah K.; Wessendorf, Ryan L.; Hines, Kevin M.; Bentolila, Stephane; Hanson, Maureen R.; Lu, Yan
Abstract : An organelle RNA recognition motif protein is required for psbF transcript editing and the production of efficient PSII in Arabidopsis. Abstract: Loss-of-function mutations in ORGANELLE RNA RECOGNITION MOTIF PROTEIN6 (ORRM6) result in the near absence of RNA editing of psbF -C77 and the reduction in accD -C794 editing in Arabidopsis ( Arabidopsis thaliana ). The orrm6 mutants have decreased levels of photosystem II (PSII) proteins, especially PsbF, lower PSII activity, pale green pigmentation, smaller leaf and plant sizes, and retarded growth. Stable expression of ORRM6 rescues the orrm6 editing defects and mutant phenotype. Unlike ORRM1, the other known ORRM plastid editing factor, ORRM6, does not contain RNA editing interacting protein/multiple organellar RNA editing factor (RIP/MORF) boxes, which are required for ORRM1 to interact with site-specific pentatricopeptide repeat protein editing factors. ORRM6 interacts with RIP1/MORF8, RIP2/MORF2, and RIP9/MORF9, known components of RNA editosomes. While some plastid RRM proteins are involved in other forms of RNA processing and translation, the primary function of ORRM6 is evidently to mediate psbF -C77 editing, like the essential site-specific pentatricopeptide repeat protein LOW PSII ACCUMULATION66. Stable expression in the orrm6 mutants of a nucleus-encoded, plastid-targeted PsbF protein from a psbF gene carrying a T at nucleotide 77 significantly increases leaf and plant sizes, chlorophyll content, and PSII activity. These transformants demonstrate that plastid RNA editing can be bypassed through the expression of nucleus-encoded, edited forms of plastid genes.